General control modulo and Tauberian remainder theorems for (C, 1) summability - Meronen, Olga; Tammeraid, Ivar (Mathematical Modelling and Analysis, 2013)
We prove for the (C, 1) summability method several Tauberian remainder theorems using the general control modulo of the oscillatory behavior.